HUKUM SEBAGAI ALAT REKAYASA SOSIAL DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KABUPATEN TANGGAMUS - Wirawan, M. Yusuf; Rudy, Rudy; Wierma Putri, Ria (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to analyze the function of law as a tool of social engineering in household waste management in Tanggamus Regency. The research method used is normative research with a legislative approach. The results of the study show that there are three regional regulations that serve as tools of social engineering in waste management in Tanggamus Regency. The law in waste management in Tanggamus Regency aims to address two main aspects: “waste handling” and the “obligations of traders and area managers.” Waste handling is organized on three scales: small, medium, and large. Meanwhile, the obligations of traders and area managers include the provision of facilities and infrastructure that cover waste sorting, collection, and processing at the regional scale.